2017
DOI: 10.3847/1538-4357/834/2/139
|View full text |Cite
|
Sign up to set email alerts
|

Radio Measurements of the Stellar Proper Motions in the Core of the Orion Nebula Cluster

Abstract: Using multi-epoch Very Large Array observations, covering a time baseline of 29.1 years, we have measured the proper motions of 88 young stars with compact radio emission in the core of the Orion Nebula Cluster (ONC) and the neighboring BN/KL region. Our work increases the number of young stars with measured proper motion at radio frequencies by a factor of 2.5 and enables us to perform a better statistical analysis of the kinematics of the region than was previously possible. 1.27 0.15 mas yr −1 . We looked f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 37 publications
5
68
1
Order By: Relevance
“…This implies that the one-dimensional velocity dispersion in Taurus is somewhat higher than the value of 1km s −1 adopted by Luhman et al (2009) and smaller than the value of 6km s −1 estimated by Bertout & Genova (2006). This value is also similar to the one-dimensional velocity dispersion obtained by Dzib et al (2017) and Kounkel et al (2017) for YSOs in the Orion Nebula Cluster.…”
Section: Taurus (All Stars)supporting
confidence: 75%
“…This implies that the one-dimensional velocity dispersion in Taurus is somewhat higher than the value of 1km s −1 adopted by Luhman et al (2009) and smaller than the value of 6km s −1 estimated by Bertout & Genova (2006). This value is also similar to the one-dimensional velocity dispersion obtained by Dzib et al (2017) and Kounkel et al (2017) for YSOs in the Orion Nebula Cluster.…”
Section: Taurus (All Stars)supporting
confidence: 75%
“…40 14.39 14.38 14.37 14.36 14.35 14.34 14.33 14.32 40 14.39 14.38 14.37 14.36 14.35 14.34 14.33 14.32 7. THE PROPER MOTIONS OF IRC23 AND ZAPATA 11 Dzib et al (2017) found that the radio sources IRc23 and Zapata 11 also seem to show proper motions receding from the same point from which the other sources are escaping. We use the four new epochs to test this hypothesis and fully confirm the significant large proper motions of these two additional sources.…”
Section: Rotation In the Radio Source?mentioning
confidence: 98%
“…The compact objects that have well measured proper motions are BN, I, n, and more recently source x, studied in the near-infrared by Luhman et al (2017). In addition, Dzib et al (2017) proposed that the sources Zapata 11 and IRc 23 may also be part of the group of receding sources.…”
mentioning
confidence: 99%
“…We estimated the errors in these motions from the standard deviations of the differences in right ascension and declination between the two epochs. These estimates are upper limits for the errors since the velocity dispersion among the stars (∼ 1 mas yr −1 , van Altena et al 1988;Dzib et al 2017) also contributes to the dispersion in our proper motion measurements.…”
Section: Astrometry In the Kleinmann-low Nebulamentioning
confidence: 99%
“…For one of these massive stars, the Becklin-Neugebauer (BN) object (Becklin & Neugebauer 1967), multi-epoch radio observations have revealed an unusually high proper motion (Plambeck et al 1995). Members of Orion exhibit a dispersion of ∼ 1 mas yr −1 in their proper motions (van Altena et al 1988;Dzib et al 2017), whereas BN has a proper motion of 13.5 mas yr −1 (26 km s −1 ) relative to the cluster .…”
Section: Introductionmentioning
confidence: 99%